PERAN BRAND AWARENESS MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION KEDAI BERBAGI RUANG DAN KOPI - I Gst Ayu Luna Purantari Putri; Putu Saroyini Piartrini (BORJUIS: JURNAL OF ECONOMY, 2025)
This study examines the effect of social media marketing on purchase intention, with brand awareness serving as a mediating variable, at Kedai Berbagi Ruang dan Kopi. Employing a quantitative approach, data were collected offline via questionnaires from 100 purposively sampled respondents active social media users in Peguyangan Kangin subdistrict. Data analysis was conducted using path analysis in SPSS version 26. The results indicate that: (1) social media marketing has a positive and significant impact on purchase intention; (2) social media marketing positively and significantly influences brand awareness; (3) brand awareness positively and significantly affects purchase intention; and (4) brand awareness positively mediates the relationship between social media marketing and purchase intention. Based on these findings, it is recommended that Kedai Berbagi Ruang dan Kopi’s management implement creative promotions such as offering discounts to followers who post stories tagging the café’s account to boost brand awareness and position the café as consumers’ preferred choice.